Determination of the Measurement of Un-signalized Intersection Elasticity for a Traffic Control System - Zhang, Hui; A., Zulkiple (Penerbit UMP, 2014)
Park-and-ride has been deployed at KTM Klang Commuter Station as to ease traffic congestion. The location of the station within the town center however invited doubt about the functionality of the park and ride facility which supposed to hijack vehicle from coming to the town center. A park and ride is supposed to be located at the fringe of a town area such that drivers and riders may opt to park their vehicles at the facility and take a public transport system as to continue their journey to the town center. This study aims to determine the measurement of traffic control system whether or not it can sustain the extra traffic demand as the outcome of the new P&R facility.